2011
DOI: 10.1177/1358863x11422571
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in diagnosing pulmonary embolism in the obese patient: A literature review

Abstract: Several of the signs and symptoms of pulmonary embolism, such as dyspnea, tachypnea, and tachycardia, are common in the obese population, so these patients are frequently suspected of having a pulmonary embolism. Establishing an accurate diagnosis in this situation is often difficult. We performed a review of the literature examining the difficulty of diagnosing pulmonary embolism in obese patients. Several factors compromise the ability of clinicians to accurately diagnose pulmonary embolism in obese patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 66 publications
(75 reference statements)
0
41
0
1
Order By: Relevance
“…2,21,22 Third, for patients with high BMI whose pretest probability or D-dimer result mandate imaging, systems should have BMI-specific protocols in place, such as increasing the volume of iodinated contrast to reduce the rate of indeterminate image results on CT angiography. 23,24 This study is limited in its estimate of radiation exposure on a per-procedure basis. As described previously, we chose this method over using data from the console report from the CT scan because we found these data unreliable and exclusive of nuclear and fluoroscopic studies, and we could find no device to directly measure radiation on or in the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,21,22 Third, for patients with high BMI whose pretest probability or D-dimer result mandate imaging, systems should have BMI-specific protocols in place, such as increasing the volume of iodinated contrast to reduce the rate of indeterminate image results on CT angiography. 23,24 This study is limited in its estimate of radiation exposure on a per-procedure basis. As described previously, we chose this method over using data from the console report from the CT scan because we found these data unreliable and exclusive of nuclear and fluoroscopic studies, and we could find no device to directly measure radiation on or in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…For example, obesity increases the probability of indeterminate findings on electrocardiography, 8 nuclear scintillation scanning of the heart or lungs, 9 and computerized tomographic pulmonary angiography (CTPA). 10,11 A study performed in navy-enlisted personnel found that evaluation for chest pain was consistently in the top 5 diagnostic-related group codes in terms of total economic expenditures for the care of obese patients of all age groups. 12 Obesity has been found to prolong the length of stay for numerous acute medical and surgical conditions.…”
mentioning
confidence: 99%
“…The two groups were: intubated, mechanically ventilated patients, and conscious non-intubated patients. Elements that contribute to suboptimal quality of CTPA studies have previously been identified as motion artefact [1][2][3][4][5] , poor peripheral pulmonary contrast flow [4,[6][7][8] , and poor contrast enhancement of the main pulmonary trunk [4,[9][10][11][12][13] .…”
Section: Institute Of Medical Research Queensland Australiamentioning
confidence: 99%
“…61 In practice the diagnosis is often made on clinical grounds once alternative diagnoses have been excluded. Commonly used radiologic imaging modalities such as computed tomography scanning are unhelpful, partly because of poor image quality in obese patients and partly because of weight limits on the scanner table.…”
Section: Venous Thromboembolism (Vte)mentioning
confidence: 99%